Building public trust: a response to COVID-19 vaccine hesitancy predicament - Vergara, Raymond John D; Sarmiento, Philip Joseph D; Lagman, James Darwin N (Journal of public health (Oxford, England), 2021)
With the rollout of vaccines against COVID-19, an optimistic and a negative attitude among people have arisen. Surprisingly, surveys among people reveal that there is a significant rate of distrust against the vaccines. In a recent short report published in this journal, vaccine hesitancy was found out among medical students. Hence, wide array of research has been springing, recommending various approaches in assisting authorities deal with vaccine hesitancy such as proper and effective strategic communication as a solution. This study suggests however that a more 'localized' public education and role-modelling from public officials and health authorities can help a lot in building public trust. The study aims to contribute to the further development of public health mechanisms in the rolling-out and distribution of vaccines against COVID-19.